Ingerência penal e proteção integral à vítima - Faloppa, Fabiola Moran (2019)
This paper aims to shed light on the legal and political-criminal treatment of victims of crime. Passing through the historical analysis, which involves the cession of its protagonism in favor of the construction of an exclusive dialectic between state and perpetrator, the constitutional influence of the International Treaties of Human Rights and the Mandates of Criminalization involving the crime victim is discussed. From this outlook, it addresses the victimological issue in the context of a Total Criminal Science, encompassing the perspective of the victim in Criminal Law, Criminology and Criminal Policy. The International Victimological Movement has a major influence on the development of the work, enabling the discussion of a global science based on victim prevention, victimization and hidden figures, as well as the need to develop occasional modifications in the traditional justice model for the reintegration of the victim in the criminal context as legitimation of state punitive power. In this sense, it is proposed the introduction of reparative practices oriented to the victims, whose main objectives are the reparation of the damage, protection and assistance to overcome the victimization trauma. The rights of victims enshrined in the international context are analysed and collated with the applicable homeland protection laws and microsystems. Finally, we highlight the importance of building a comprehensive protection system, recognizing to the Public Prosecutor the mission of improving its practices and performance, in view of its constitutional vocation